Frequency of achieving a 'fit' cardiorespiratory fitness level and hypertension: a cohort study. Issue 4 (April 2019) - Momma, Haruki; Sawada, Susumu S.; Sloan, Robert A.; Gando, Yuko; Kawakami, Ryoko; Miyachi, Motohiko; Fukunaka, Yasushi; Okamoto, Takashi; Tsukamoto, Koji; Nagatomi, Ryoichi; Blair, Steven N.
Abstract : Objectives: Although maintaining cardiorespiratory fitness is encouraged to reduce the risk of hypertension, the level at, and length of time for which, individuals need to maintain fitness remains unclear. We examined the association between the frequency of achieving the recommended fitness levels of the 'Physical Activity Reference for Health Promotion 2013' and the risk of hypertension among Japanese men. Methods: This cohort study was conducted in 6653 men without hypertension enrolled in 1986. Whether the participants' fitness level was equal to or exceeded the reference value (fit) or not (unfit) was determined. The frequency of achieving the recommended fitness level was calculated by counting the number of times the fitness level was achieved in 1980 through 1986. Incident hypertension was defined as the first visit with a SBP/DBP of at least 140/90 mmHg or self-reported antihypertensive medication use and was evaluated during annual health examinations from 1986 until 2009. Results: During the follow-up period, 3630 men developed hypertension. The multivariable-adjusted hazard ratios (95% confidence interval) for incident hypertension comparing men with fit versus unfit at baseline was 0.79 (0.74–0.85). Moreover, the frequency of achieving the recommended fitness level was inversely associated with the incidence of hypertension. The risk of hypertension was lower among those who achieved three or more of the recommended levels (0.72 for three times to 0.62 for seven times). Conclusion: Achieving the fitness level recommended in the Japanese guideline three or more times during a 6-year period can be beneficial for the risk reduction of hypertension. Abstract : Supplemental Digital Content is available in the text